Reactive Hyperemia Occurs Via Activation of Inwardly Rectifying Potassium Channels and Na+/K+-ATPase in Humans - Crecelius, Anne R.; Richards, Jennifer C.; Luckasen, Gary J.; Larson, Dennis G.; Dinenno, Frank A. (Circulation research, 2013)
RATIONALE:Reactive hyperemia (RH) in the forearm circulation is an important marker of cardiovascular health, yet the underlying vasodilator signaling pathways are controversial and thus remain unclear. OBJECTIVE:We hypothesized that RH occurs via activation of inwardly rectifying potassium (KIR) channels and Na/K-ATPase and is largely independent of the combined production of the endothelial autocoids nitric oxide (NO) and prostaglandins in young healthy humans. METHODS AND RESULTS:In 24 (23±1 years) subjects, we performed RH trials by measuring forearm blood flow (FBF; venous occlusion plethysmography) after 5 minutes of arterial occlusion. In protocol 1, we studied 2 groups of 8 subjects and assessed RH in the following conditions. For group 1, we studied control (saline), KIR channel inhibition (BaCl2), combined inhibition of KIR channels and Na/K-ATPase (BaCl2 and ouabain, respectively), and combined inhibition of KIR channels, Na/K-ATPase, NO, and prostaglandins (BaCl2, ouabain, L-NMMA [N-monomethyl-L-arginine] and ketorolac, respectively). Group 2 received ouabain rather than BaCl2 in the second trial. In protocol 2 (n=8), the following 3 RH trials were performedcontrol; L-NMMA plus ketorolac; and L-NMMA plus ketorolac plus BaCl2 plus ouabain. All infusions were intra-arterial (brachial). Compared with control, BaCl2 significantly reduced peak FBF (−50±6%; P<0.05), whereas ouabain and L-NMMA plus ketorolac did not. Total FBF (area under the curve) was attenuated by BaCl2 (−61±3%) and ouabain (−44±12%) alone, and this effect was enhanced when combined (−87±4%), nearly abolishing RH. L-NMMA plus ketorolac did not impact total RH FBF before or after administration of BaCl2 plus ouabain. CONCLUSIONS:Activation of KIR channels is the primary determinant of peak RH, whereas activation of both KIR channels and Na/K-ATPase explains nearly all of the total (AUC) RH in humans.